ALOKASI ANGGARAN PENDIDIKAN DALAM ANGGARAN PENDAPATAN DAN BELANJA NEGARA (APBN) DI INDONESIA - Rustiningrum, Sri; Digdowiseiso, Kumba (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. Education as a learning tool that can increase insight and knowledge and make the community have more value and be able to explore and develop them existing potentials, so that they become quality human resources. The government provides an allocation of education funds with a minimum amount of 20% of the total state budget each year. With this high budget allocation, education in Indonesia should be able to reach all people. However, children drop out of school still happen because of motivation and economic factors. Most of the education budget allocation is still used for the payment of salaries for teachers so that the education quality has not been considered, even though it should be with a large budget that the education quality can be improved and developed. The purpose of this study is to find out how the education budget allocations in the APBN in Indonesia. The research method is to conduct a literature review. The results obtained are: 1. Education budget is allocated more for local governments than for the central government. 2. Indonesia has a large proportion of the expenditure budget and this budget is mostly used to pay teachers. 3. There has been no effort to improve the quality of education that has been able to motivate people to attend education.